2006
DOI: 10.1562/2005-05-08-ra-52
|View full text |Cite
|
Sign up to set email alerts
|

Conidial Pigmentation Is Important to Tolerance Against Solar‐simulated Radiation in the Entornopathogenic Fungus Metarhizium anisopliae

Abstract: The importance of conidial pigmentation to solar UV radiation tolerance in the entomopathogenic fungus Metarhizium anisopliae var. anisopliae, was estimated by comparing the effects of exposure to simulated solar UV radiation on the wild-type parent strain U.S. Department of Agriculture (USDA)-Agricultural Research Service (ARS) Collection of Entomopathogenic Fungal Cultures (ARSEF) 23, which has dark green conidia, and three groups of color mutants with yellow, purple and white conidia. The comparisons includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
23

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 40 publications
2
34
0
23
Order By: Relevance
“…Variation in susceptibility of entomopathogenic fungi to UV was also related to the color of conidia, since conidial pigmentation seems to be very efficient in protecting against UV radiation, directly (Braga et al 2006;Rangel et al 2006b;Nascimento et al 2010), or indirectly because enzymes involved in pigment-synthesis pathways are also required for tolerance to abiotic stresses (Fang et al 2010). A study conducted with simulated ultraviolet sunlight reported that conidial color can influence the inactivation of conidia by the radiation, where the UV radiation may be blocked on black conidia whereas penetration of UV may vary for other pigmented conidia (Ignoffo and Garcia 1992).…”
Section: Seeking Fungal Isolates Naturally Tolerant To Uvmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in susceptibility of entomopathogenic fungi to UV was also related to the color of conidia, since conidial pigmentation seems to be very efficient in protecting against UV radiation, directly (Braga et al 2006;Rangel et al 2006b;Nascimento et al 2010), or indirectly because enzymes involved in pigment-synthesis pathways are also required for tolerance to abiotic stresses (Fang et al 2010). A study conducted with simulated ultraviolet sunlight reported that conidial color can influence the inactivation of conidia by the radiation, where the UV radiation may be blocked on black conidia whereas penetration of UV may vary for other pigmented conidia (Ignoffo and Garcia 1992).…”
Section: Seeking Fungal Isolates Naturally Tolerant To Uvmentioning
confidence: 99%
“…Accordingly, the black conidia of Aspergillus niger presented a remarkably higher mean half-life of 14.8 h when exposed to simulated sunlight than those of all other species investigated, which included less-pigmented conidia of Beauveria, Nomuraea, Metarhizium, and a tancolored mutant of A. niger, with a half-life ranging from 1.1 h for Nomuraea rileyi to 2 h for the tan-colored mutant A. niger (Ignoffo and Garcia 1992). Color mutants of the darkly pigmented conidia M. robertsii wild-type ARSEF 23 were, in general, significantly more tolerant to UV than the less-pigmented conidia of its mutants (Braga et al 2006;Rangel et al 2006b;Nascimento et al 2010). Conversely, other studies report that the hyaline conidia of B. bassiana s.l.…”
Section: Seeking Fungal Isolates Naturally Tolerant To Uvmentioning
confidence: 99%
“…Incubation was in the dark at 28 C for 12 days, as previously described (Braga et al 2006). After growth, mature conidia were carefully harvested, frozen in liquid nitrogen, and stored at À80 C until use.…”
Section: Conidia Productionmentioning
confidence: 99%
“…As both solar UV-A and UV-B can kill the conidia, as well as limit the proliferation and dispersion of fungi, it is important to summarize the available knowledge of the effects of solar radiation on conidia and on the major systems involved in the protection and repair of damage induced by solar UV radiation. The authors also assure the importance of the fungal pigmentation on conidial UV tolerance as published elsewhere (Braga et al 2006;Rangel et al 2006b). The review demonstrated that it is possible to manipulate fungi in laboratory conditions so that the resulting strains produce conidia that are more tolerant to solar radiation than wild type.…”
Section: Topics Covered In This Special Issuementioning
confidence: 68%